Soluble metal material dissolving property testing method considering system error

Through the testing method that simulates real application conditions, the dissolution performance problem under galvanic corrosion and crevice corrosion conditions in the prior art was solved, and more accurate dissolution rate calculation and more realistic dissolution performance evaluation were achieved.

CN119413696APending Publication Date: 2025-02-11CNOOC ENERGY TECHNOLOGY & SERVICES LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411525848.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-30
Publication Date
2025-02-11

AI Technical Summary

Technical Problem

The existing dissolution testing methods fail to effectively consider the dissolution performance of soluble metal materials under galvanic corrosion and crevice corrosion conditions, and fail to accurately measure dissolution weight loss, resulting in systematic errors in the calculation of dissolution rate.

Method used

Provide a method for testing the dissolution performance of soluble metal materials that consider system errors. By simulating real application conditions, using test tooling and dissolving media, measuring the mass and shape changes of samples, calculating the dissolution rate, simplifying the test process and eliminating it System error.

Benefits of technology

This method can more accurately reflect the corrosion laws, consider electrochemical corrosion, galvanic corrosion and crevice corrosion, eliminate system errors, and provide a more realistic assessment of the dissolution performance of soluble metal materials under operating conditions.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119413696A_ABST
    Figure CN119413696A_ABST
Patent Text Reader

Abstract

The invention discloses a soluble metal material dissolving property testing method considering system errors, which comprises the following steps: designing the structure of a soluble metal material, processing the soluble metal material into a test sample piece, customizing a test tool, preparing a dissolving medium, measuring the quality of the sample piece, or fixing the sample piece on the test tool, and measuring the heights of the upper end surface and the lower end surface of the sample piece. The method comprises the following steps: placing a test tool fixed with a sample piece in a device filled with a dissolving medium, heating and stabilizing at a certain temperature to carry out a dissolving test, taking out the tool and the sample piece at regular intervals, carrying out post-treatment, measuring the mass of the dissolved sample piece or the height of the sample piece on the upper and lower end faces of the tool, and calculating the dissolving rate. According to the invention, various types of soluble metal materials can be simulated to be used as temporary plugging parts of oil and gas well tools in the oil and gas industry for dissolution testing, so that the dissolution performance of the temporary plugging parts under different working conditions is comprehensively evaluated.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of material corrosion, and in particular to a method for testing the dissolution performance of soluble metal materials taking system errors into consideration. Background Art

[0002] Soluble magnesium alloys and zinc alloys have excellent mechanical properties and suitable solubility. They are excellent materials for temporary plugging components of oil and gas well tools in the oil and gas industry. Temporary plugging components can selectively isolate the reservoir when plugging is required. When the operation is completed, the soluble temporary plugging components dissolve by themselves in the downhole temperature and pressure environment to open up the wellbore to achieve oil and gas extraction, which can save operating procedures, improve production efficiency, and have broad application prospects. In the process of developing a series of suitable temporary plugging tools, it is necessary to conduct a series of tests and evaluations on the solubility performance of temporary plugging tool components in combination with application scenarios. However, most of the known dissolution test methods and corrosion test literature are based on weightlessness immersion tests for evaluation, or some simple electrochemical tests for application scenarios. The test conditions, error elimination methods and dissolution rate expression methods are different. Most of the test methods do not take into account the working conditions of the material and its metal fittings, nor do they consider the galvanic corrosion and the influence of installation gaps on dissolution.

[0003] Therefore, it is necessary to carefully and effectively evaluate the dissolution performance of soluble metal temporary plugging components to simplify and solve the problem of not being able to accurately measure dissolution weight loss under galvanic corrosion conditions in the past. Summary of the invention

[0004] In order to solve the above technical problems, the present invention provides a method for testing the dissolution performance of soluble metal materials taking into account system errors. The method simulates the actual conditions for the application of soluble metal materials and can observe various types of dissolution scenarios (such as different materials, structures, shapes, surface areas, different potential differences of galvanic corrosion, etc.), thereby comprehensively evaluating the dissolution performance of soluble metal materials under operating conditions.

[0005] The present invention is achieved by adopting the following technical solutions.

[0006] A method for testing the dissolution performance of soluble metal materials taking into account system errors comprises the following steps:

[0007] S1. Prepare the samples to be tested;

[0008] S2. Corresponding customized test tooling;

[0009] S3. preparing a dissolution medium;

[0010] S4. Measure the mass of the sample, or after fixing the test sample on the test fixture, use a depth caliper to measure the height of the upper and lower end surfaces of the test sample from the edge of the fixing fixture;

[0011] S5. Place the test fixture with the test sample fixed in a device containing a dissolving medium, heat it to a certain temperature and perform a dissolution test. The test fixture can simulate the galvanic corrosion and crevice corrosion working conditions of the test sample;

[0012] S6. Take out the test sample and the test fixture at regular intervals, perform post-processing, measure the sample mass or use a depth caliper to measure the height of the upper and lower end faces of the test sample from the edge of the fixed fixture again, compare the difference in dissolved mass or height, and calculate its dissolution rate. This application takes into account the galvanic corrosion and crevice corrosion between the sample and the fixture. The method is simple, efficient, and easy to operate, eliminating the systematic error in the measurement process, making the dissolution rate calculation result more realistic.

[0013] Furthermore, the test sample is a soluble metal material, and the materials include magnesium-aluminum alloy and magnesium-zinc alloy; in combination with the use scenario of the soluble metal material, the structure or shape of the test sample is designed and processed into parts of different shapes, including pin-shaped, ball-shaped, ball seat-shaped, ball valve-shaped or plate valve-shaped, which are consistent with the usage form under actual working conditions; before testing, the surface is cleaned and free of obvious contaminants.

[0014] Furthermore, the material of the test tooling is consistent with the application scenario of the temporary plugging component, the structure and size of the temporary plugging component installed on the tooling are consistent with the application scenario of the temporary plugging component, and the structure of the test tooling includes one or more of a sealing step, annular groove, retaining ring groove, threaded surface, groove, sealing surface, and step surface; during testing, the test sample is fixed on the test tooling.

[0015] Furthermore, according to the requirements of the application scenario, the dissolving medium is selected from 6000-100000 mg / L sodium chloride solution or salt water, hydrogen sulfide solution, and supercritical carbon dioxide solvent.

[0016] Furthermore, the device containing the dissolving medium is a heating device, and the measuring temperature is set to 50-200°C, which is consistent with the temperature of the material application scenario, and the dissolving time is at least 48 hours. The concentration, temperature and time of the medium in this application can be tested by simulating actual working conditions.

[0017] Furthermore, the post-processing method is: rinse the test sample and the test fixture taken out from the dissolution medium with clean water, remove the dissolution products on the surface of the test sample and the test fixture, absorb the moisture on the surface of the test sample and the test fixture, and record its appearance photos to facilitate comparison with various parameters before and after the dissolution test.

[0018] Furthermore, the dissolution rate is calculated based on the dissolution mass difference or height difference of electrochemical corrosion, galvanic corrosion and crevice corrosion per unit time, and the dissolution rate is calculated by formulas A-1, A-2 and A-3;

[0019] Dissolution rate:

[0020]

[0021] μ, dissolution rate, Kgm2×t, mm / day or mm / h

[0022] t, time, h

[0023] volume:

[0024] V=Sh............(A-2)

[0025] V, volume, m 3

[0026] S, area, m 2

[0027] h, height, m

[0028] quality:

[0029] m=ρV............(A-3)

[0030] m, mass, Kg

[0031] ρ, density, kg / m 2 .

[0032] This application has the following beneficial effects.

[0033] The present invention only requires basic measuring equipment such as test fixtures, balances, depth calipers, etc. to meet various test requirements. The method of the present invention can more accurately reflect the corrosion law, taking into account the electrochemical corrosion of soluble metal materials and the galvanic corrosion and crevice corrosion between different metal connections. By measuring the difference calculation, the system error can be effectively eliminated. At the same time, combined with the analysis of measurement data, the dissolution behavior of soluble metal materials can be explained and predicted, so as to effectively design the structure / shape and accurately control the temporary plugging components. BRIEF DESCRIPTION OF THE DRAWINGS

[0034] Figure 1 is a schematic diagram of the structure of the test sample in Example 1 of the present invention (pin);

[0035] Figure 2 is a schematic diagram of the structure of the test tool in Example 1 of the present invention;

[0036] Figure 3 It is a front and back physical picture of the test tool and the tested sample before the dissolution test of Example 1 of the present invention;

[0037] Figure 4It is a front and back physical picture of the test tool and the sample to be tested during the dissolution test process of Example 1 of the present invention;

[0038] Figure 5 This is a front and back physical picture of the test fixture and the tested sample after some pins are dissolved in Example 1 of the present invention;

[0039] Figure 6 is a schematic structural diagram of a test sample in Example 2 of the present invention (soluble plate valve);

[0040] Figure 7 is a schematic diagram of the structure of the test tool in Example 2 of the present invention;

[0041] Figure 8 is a schematic diagram of the structure of the test sample in Example 3 of the present invention (soluble ball);

[0042] Fig. 9 is a schematic diagram of the structure of the test tool in Example 3 of the present invention;

[0043] Fig.10 It is a flow chart of the dissolution performance testing method of the soluble metal material of the present invention.

[0044] Among them, 1. thread; 2. base; 3. soluble valve plate; 4. valve seat; 5. sealing ring; 6. torsion spring; 7. soluble ball; 8. ball seat. DETAILED DESCRIPTION

[0045] The present patent application is further described below in conjunction with embodiments.

[0046] Unless otherwise specified, the experimental methods used in the following preparation examples and examples are all conventional methods; the materials, reagents, etc. used in the following preparation examples and examples are all commercially available unless otherwise specified.

[0047] Example 1

[0048] A method for testing the dissolution performance of soluble metal materials taking into account system errors comprises the following steps:

[0049] Step 1: Prepare the sample of the soluble metal material to be tested.

[0050] The tested samples shall be Figure 1 Processed into a pin shape, the sample size is preferably: 12mm in diameter, 30mm in height, 10mm in thread end, and made of aluminum-magnesium alloy. To ensure the authenticity and accuracy of the test, the number of tests per batch should be at least 3. The surface should be kept clean and free of oil before testing. If there is oil, it should be cleaned to ensure that it has no effect on the sample solubility test.

[0051] The second step is to prepare the dissolving medium. Usually, oil and gas well tools are often placed in drilling and completion fluids or seawater for operation, so sodium chloride solution with the same chloride ion concentration is directly selected to simulate the actual use environment. Of course, other corrosive solutions can also be selected as dissolving media.

[0052] Step 3: Refer to Figure 2 Design and process the test fixture, and fix the above-mentioned samples on the fixture. Test the distance between the samples and the upper and lower end surfaces of the fixture, and record the appearance photos for comparison with the parameters after the dissolution test.

[0053] The fourth step is to place the test sample and the device in a constant temperature water bath containing sodium chloride solution to test the dissolution performance. The bottom hole circulation temperature usually ranges from 50-200℃. When it is below 90℃, a water bath is used for heating. When it is 100-200℃, a high temperature hydrothermal reactor is used for simulation. During the dissolution test, the test device is filled with the dissolution medium.

[0054] There is a distance between the sample and the equipment on each side, the bottom distance range is 1-3mm, and the top is at least 10mm higher than the sample.

[0055] In actual tests, soluble metal material samples are usually fixed on a tool and placed in a dissolving medium. Usually, the tool can be made of 4145H steel / (42CrMo steel for high temperature) and other steel materials commonly used in oil and gas well tools. Since galvanic corrosion will occur when different metals are in direct contact in a dissolving medium, and crevice corrosion will occur when there is a gap between different metals, galvanic corrosion will usually occur at the contact point between the pin and the tool during actual use, and crevice corrosion will usually occur at the connection gap between the pin and the tool. The tool provided by the present invention will test the galvanic corrosion and crevice corrosion of soluble metal materials during actual use.

[0056] like Figure 2 As shown, a certain number of circular holes are set on the test fixture, the upper diameter of the circular hole is larger than the major diameter of the lower thread, and a certain length of the lower part of the circular hole is set as a thread, which is used to match the lower thread of the tested sample for installation. The tested sample is a cylindrical structure, the upper part is a circular surface, and the lower part is a certain length of thread 1 that matches the lower part of the tooling, and the diameter of the upper circular surface is larger than the major diameter of the lower thread. The tested sample is connected and fixed with the circular hole of the tooling (threaded connection). The upper and lower end faces of the tested sample are directly in contact with the dissolving medium respectively, which meets the conditions of galvanic corrosion, and the corrosion of the upper and lower end faces of the pin can be observed at any time. And by setting different thread lengths and thicknesses, the effect of the gap size on the crevice corrosion can be tested. There is a gap between the sample and the tooling, which meets the conditions of crevice corrosion. Therefore, the test fixture can test galvanic corrosion and crevice corrosion at the same time.

[0057] When the temperature of the sodium chloride solution reaches 60°C, the timing starts. The test time needs to be at least 48 hours, preferably 48 hours, 72 hours, 168 hours, 240 hours, 360 hours, etc.

[0058] During the entire test process, the chloride ion concentration of the sodium chloride solution needs to be measured with a chloride ion meter at intervals of up to 72 hours, and it needs to be circulated and replaced in a timely manner to ensure the stability of the dissolved medium concentration and the accuracy of the test.

[0059] The fifth step is to post-process the tested samples and tooling at regular intervals, and measure the height of the post-processed samples from the upper and lower ends of the tooling.

[0060] After the dissolution test is completed, there is no need to remove the sample from the tooling. Rinse the tooling and sample with running water to remove the dissolution products that are not firmly attached. Wipe off the residual water on the surface of the tooling and the remaining sample. Use a depth caliper to measure the height of the two end faces of the sample from the fixed edge of the tooling, and compare it with the initial height before the test to calculate the difference in dissolved height between the upper and lower end faces. Note that each measurement should be made at the same position of the sample and the tooling as much as possible. Record appearance photos (such as Figure 3 , 4 , 5), the test sample has powdery or ring-shaped corrosion products, the edge corrodes to form a convex column, the middle corrodes first to form a groove, or the thread end dissolves first, causing the sample to fall off the tooling, all of which should be recorded. If it falls off, the height of the fallen sample should be recorded, and the difference with the initial height before the test should be calculated to calculate the dissolution rate (mm / day). The experimental results are shown in Table 1.

[0061] Table 1 Dissolution rate record of soluble pins at 160℃ and 18000mg / L chloride ion concentration

[0062] Time interval (days) 2 3 5 8 10 Dissolution height difference between upper and lower end surfaces (mm) 5.35 6.40 8.67 12.43 — Dissolution rate / (mm / day) 2.68 2.13 1.73 1.55 —

[0063] Example 2

[0064] Soluble Plate Valve Test Solution

[0065] The soluble plate valve tool is mainly used for temporary plugging of oil and gas flow channels in the petroleum industry. The tool works by using a torsion spring, valve seat and base to fix the plate valve, achieving temporary plugging of oil and gas for a certain period of time. The plate valve dissolves within the designed time to connect the oil and gas channels.

[0066] Soluble plate valve design Figure 6 To ensure that the test fully simulates the application scenario of the soluble plate valve, the tooling is designed as follows Figure 7As shown: the test tool consists of a base 2, a torsion spring 6, a soluble plate valve 3, a valve seat 4, and a sealing ring 5, wherein the base 2 and the valve seat 4 are both steel structures, the base 2 is a hollow cylindrical structure to ensure that the lower part of the valve plate can contact the solution, the torsion of the torsion spring 6 can fix the valve plate above the base 2, and the entire test tool is placed in a water bath to test the quality of the soluble plate valve before and after dissolution within a certain period of time, and the test tool is connected to the pressure test joints above and below to test the sealing effect of the plate valve after dissolution for a certain period of time under the pressure required by the tool application scenario.

[0067] Example 3

[0068] Soluble ball seat test solution

[0069] The soluble ball is mainly used to block the oil and gas channels, increase the pressure in the flow channel, and assist in realizing the design functions of oil tools such as sliding sleeves, release valves, and throttle valves. After a certain period of time, the soluble ball gradually dissolves and connects the oil and gas channels. A conical ball seat will be set in the above-mentioned tools to support the ball.

[0070] Soluble ball design Figure 8 In order to ensure that the test completely simulates the application scenario of the soluble ball, the tooling is designed as shown in Figure 9: the test tooling consists of a hollow cylindrical steel structure. The lower part of the tooling is designed with threads for installing a plug to facilitate the tooling pressure test. The outer circumference of the tooling is designed with a certain length of threads for connecting the pressure test joint. The entire test tooling is placed in a water bath to test the quality before and after dissolution. The lower end of the test tooling is connected to the plug and the upper end is connected to the pressure test joint to test the sealing effect of the soluble ball after it has been dissolved for a certain period of time under the pressure required by the tool application scenario.

[0071] The embodiments of this specific implementation method are all preferred embodiments of the present invention, and are not intended to limit the protection scope of the present invention. Therefore, any equivalent changes made based on the structure, shape, and principle of the present invention should be included in the protection scope of the present invention.

Claims

1. A method for testing the dissolution performance of soluble metal materials taking into account system errors, characterized in that: The following steps are involved: S1. Prepare the samples to be tested; S2. Corresponding customized test tooling; S3. preparing a dissolution medium; S4. Measure the mass of the sample, or after fixing the test sample on the test fixture, use a depth caliper to measure the height of the upper and lower end surfaces of the test sample from the edge of the fixing fixture; S5. Place the test device with the test sample fixed in a device containing a dissolution medium, heat it to a certain temperature and perform a dissolution test; S6. Take out the test sample and test fixture at regular intervals for post-processing, measure the sample mass or use a depth caliper to measure the height of the upper and lower end surfaces of the test sample from the edge of the fixed fixture again, compare the difference in dissolved mass or height, and calculate its dissolution rate.

2. A method for testing the dissolution performance of soluble metal materials taking into account system errors according to claim 1, characterized in that: The test sample is a soluble metal material, including magnesium-aluminum alloy and magnesium-zinc alloy. The test sample is designed with a structure or shape based on the usage scenario of the soluble metal material and processed into components of different shapes, including pin-shaped, spherical, ball seat-shaped, ball valve-shaped or plate valve-shaped. The surface is cleaned before testing to eliminate obvious contaminants.

3. A method for testing the dissolution performance of soluble metal materials taking into account system errors according to claim 1, characterized in that: The material of the test tooling is consistent with the application scenario of the temporary plugging component, the structure and size of the temporary plugging component installed on the tooling are consistent with the application scenario of the temporary plugging component, and the structure of the test tooling includes one or more of a sealing step, annular groove, retaining ring groove, threaded surface, groove, sealing surface, and step surface; during testing, the test sample is fixed on the test tooling.

4. A method for testing the dissolution performance of soluble metal materials taking into account system errors according to claim 1, characterized in that: According to the requirements of the application scenario, the dissolving medium is selected from 6000-100000 mg / L sodium chloride solution or salt water, hydrogen sulfide solution, and supercritical carbon dioxide solvent.

5. A method for testing the dissolution performance of soluble metal materials taking into account system errors according to claim 1, characterized in that: The device containing the dissolving medium is a heating device, and the measuring temperature is set to 50-200°C, which is consistent with the temperature of the material application scenario, and the dissolution time is at least 48 hours.

6. A method for testing the dissolution performance of soluble metal materials taking into account system errors according to claim 1, characterized in that: The post-processing method is: rinse the test samples and test fixtures taken out from the dissolution medium with clean water, remove the dissolved products on the surface of the test samples and test fixtures, absorb the moisture on the surface of the test samples and test fixtures, and record their appearance photos to facilitate comparison with various parameters before and after the dissolution test.

7. A method for testing the dissolution performance of soluble metal materials taking into account system errors according to claim 1, characterized in that: The dissolution rate is calculated based on the dissolution mass difference or height difference of electrochemical corrosion, galvanic corrosion and crevice corrosion per unit time. The dissolution rate is calculated using formulas A-1, A-2 and A-3. Dissolution rate: μ, dissolution rate, Kgm2×t, mm / day or mm / h t, time, h volume: V=Sh........................(A-2) V, volume, m 3 S, area, m 2 h, height, m quality: m=ρV................(A-3) m, mass, Kg ρ, density, kg / m 2 .